AEROBIC AND ANAEROBIC EXERCISE ABILITY OF ATHLETES COMBINED WITH BALANCED NUTRITION - Heweiqi (2021)
ABSTRACT Balanced nutrition is very important for athletes’ health and competition performance, and balanced nutrition has become a hot topic in the sports industry. In this study, 30s anaerobic work test and maximal oxygen uptake test were used to test anaerobic exercise ability and aerobic exercise ability, respectively. Four groups were set up in the two test methods, and the corresponding functional test indexes, heart rate recovery index and blood lactic acid recovery value were determined. The anaerobic capacity test showed that the maximum power of male athletes in the experimental group had significant statistical difference before and after dietary balance management, and the fatigue index of female athletes in the experimental group had a significant downward trend. Five minutes and nine minutes after exercise, the blood lactic acid value of males in the experimental group was lower than before balanced nutrition. The aerobic capacity test showed that the exhaustion time of male athletes in the experimental group was significantly different before and after balanced nutrition. After the balanced nutrition, the blood lactic acid value of male athletes in the experimental group was lower than before the management immediately and nine minutes after exercise, and the heart rate value of the male athletes in the experimental group was far lower than before the management.